« Les feuilletons de la réalité en Amérique du Nord » : l’affaire Lindbergh dans la presse espagnole, 1932-1936 - Santiago Díaz Lage (Contextes)
The object of this article is to reconstruct the reactions to the Lindbergh affair in the Spanish press from 1932 to 1936. Through a minute exam of several daily and weekly newspapers we may see how the account of this matter was determined by the stereotypes concerning U.S. society, on the one hand, and the ideological polarization of the Spanish media, on the other.